Development of magnetoresistive sensors based on planar Hall effect for applications to microcompass - Montaigne, François; Schuhl, Alain; Van Dau, Frédéric Nguyen; Encinas, Armando (Sensors and actuators. A. Physical., 2000)
We present here a new magnetoresistive sensor based on planar Hall effect for detection of low magnetic fields (10 nT) in the 1–1000 Hz frequency range. These sensors are suitable for low-cost fabrication. The growth of a Permalloy (FeNi) active layer by conventional sputtering on misoriented silicon substrates leads to a well controlled in-plane uniaxial magnetic anisotropy. Moreover, a magnetisation switching system allows to remove any offset of the measure. The association of two orthogonal sensors will give a micro-compass with an angular resolution, below 0.5°, limited by the precision of assembling, with a device size of the order of 1 mm 2.